2020
DOI: 10.1029/2020gl090534
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal Dependent Impact of Ice Cloud Longwave Scattering on the Polar Climate

Abstract: Most climate models neglect cloud longwave (LW) scattering because scattering is considered negligible compared to strong LW absorption by clouds and greenhouse gases. While this rationale is valid for simulating extrapolar regions, it is questionable for the polar regions, where the atmosphere is dry and hence has weak absorption, and ice clouds that have strong scattering capability frequently occur. Using the slab-ocean Community Earth System Model, we show that ice cloud LW scattering can warm winter surfa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(19 citation statements)
references
References 34 publications
2
17
0
Order By: Relevance
“…Similar latitudinal patterns and seasonal dependence also appear in the zonalmean surface skin temperature (Figure 3a; also Figure S2 for spatial distribution) and surface downward LW flux (Figure 3b). Like what has been shown in Chen et al (2020), downward LW flux at the surface is positively correlated with surface skin temperature (𝑟 = 0.95 for DJF and 𝑟 = 0.69 for JJA). Such a seasonally dependent Arctic warming pattern is also similar to the pattern caused by the increase of CO2 (Figure S3).…”
Section: Temperature Response In Different Climate Zonessupporting
confidence: 76%
See 4 more Smart Citations
“…Similar latitudinal patterns and seasonal dependence also appear in the zonalmean surface skin temperature (Figure 3a; also Figure S2 for spatial distribution) and surface downward LW flux (Figure 3b). Like what has been shown in Chen et al (2020), downward LW flux at the surface is positively correlated with surface skin temperature (𝑟 = 0.95 for DJF and 𝑟 = 0.69 for JJA). Such a seasonally dependent Arctic warming pattern is also similar to the pattern caused by the increase of CO2 (Figure S3).…”
Section: Temperature Response In Different Climate Zonessupporting
confidence: 76%
“…Their simulations showed a 1.0~2.0 K increase in the seasonal-mean surface air temperature over the polar region, which is at least twice as fast as that in the tropics. As a cursory study, Chen et al (2020) also identified the strong correlations between the polar surface air temperature change and the change of polar surface downward LW flux. However, the analysis by Chen et al (2020) is largely confined to the polar region without examining possible connections between extra-polar and polar regions (Holland & Bitz, 2003;Stuecker et al, 2018).…”
Section: Introductionmentioning
confidence: 89%
See 3 more Smart Citations